2011
DOI: 10.1038/cddis.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

A functionalized single-walled carbon nanotube-induced autophagic cell death in human lung cells through Akt–TSC2-mTOR signaling

Abstract: Nanoparticles are now emerging as a novel class of autophagy activators. Functionalized single-walled carbon nanotubes (f-SWCNTs) are valuable nanomaterials in many industries. This article is designed to assess the autophagic response for f-SWCNTs exposure in vitro and in vivo. A few types of f-SWCNTs were screened in human lung adenocarcinoma A549 cells for the autophagic response and related pathways in vitro. Formation of autophagosomes and LC3-II upregulation were confirmed on the basis of electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(101 citation statements)
references
References 35 publications
2
99
0
Order By: Relevance
“…In addition to our recent studies showing that autophagy mediates cigarette smoking-induced lung epithelial damage (2,4,5,36), other works have also demonstrated that autophagy positively regulates lung injury induced by influenza H5N1 (33,38), nanomaterials (21,23), and ventilation (24). Thus inhibition of autophagy might represent a valuable therapeutic target in certain lung diseases (30), and preservation of Cav-1 might acquire therapeutic benefits in these diseases.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to our recent studies showing that autophagy mediates cigarette smoking-induced lung epithelial damage (2,4,5,36), other works have also demonstrated that autophagy positively regulates lung injury induced by influenza H5N1 (33,38), nanomaterials (21,23), and ventilation (24). Thus inhibition of autophagy might represent a valuable therapeutic target in certain lung diseases (30), and preservation of Cav-1 might acquire therapeutic benefits in these diseases.…”
Section: Discussionmentioning
confidence: 71%
“…10 So far, findings have presented a paradox: some reported that the autophagy induced by NPs could promote cell death, but in other conditions it could be a protective role in response to toxicity caused by NPs. 1,11,12 To the best of our knowledge, there is no report on autophagy caused by SPIONs in human monocyte cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 For example, single wall carbon nanotubes (SWCNTs) modified by the addition of phenyl-(COOH) 2 functional groups has demonstrated a stronger cytotoxic effect than SWCNT-phenyl-SO 3 H. 13 Furthermore, COOH functionalized CNTs significantly induced autophagic cell death in human lung cells when compared to polyaminobenzenesulfonic acid (PABS) and polyethylene glycol (PEG) functionalized SWCNTs. 14 These studies suggest that the transformation of CNTs in the environment, resulting in their functionalization, has the potential to alter their toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%